2012
DOI: 10.1021/jp211955v
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Physicochemical Properties of the First Ceria Monolayer on Cu(111)

Abstract: Discontinuous ceria layers on Cu(111) represent heterogeneous catalysts with notable activities in water− gas shift and CO oxidation reactions. Ultrathin ceria islands in these catalysts are composed of monolayers of ceria exhibiting CeO 2 (111) surface ordering and bulklike vertical stacking (O−Ce−O) down to a single ceria monolayer representing the oxide-metal interface. Scanning tunneling microscopy (STM) reveals marked differences in strain buildup and the structure of oxygen vacancies in this first ceria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 57 publications
1
33
0
Order By: Relevance
“…In general, the presence of a metal support has been shown to induce important modifications in the structure and electronic properties of supported oxide films. In cerium oxide ultrathin films the interaction with the metallic substrate has been hypothesized to be responsible for the formation of ordered arrays of oxygen vacancies either on the surface 11 of a thin film or at the interface 37 . In the specific case of Pt we have shown that an in-plane lattice contraction is induced by epitaxy in ultrathin films 38 , and we detected a non-negligible Ce 3+ concentration at the interface 35 .…”
Section: Resultsmentioning
confidence: 99%
“…In general, the presence of a metal support has been shown to induce important modifications in the structure and electronic properties of supported oxide films. In cerium oxide ultrathin films the interaction with the metallic substrate has been hypothesized to be responsible for the formation of ordered arrays of oxygen vacancies either on the surface 11 of a thin film or at the interface 37 . In the specific case of Pt we have shown that an in-plane lattice contraction is induced by epitaxy in ultrathin films 38 , and we detected a non-negligible Ce 3+ concentration at the interface 35 .…”
Section: Resultsmentioning
confidence: 99%
“…The metal work function has been shown to determine the charge transfer at the interface between ultrathin oxide films supported on single crystalline metal surfaces . Therefore, the larger charge transfer reported between CeO 2 films and other metal supports, like Cu(111), Ag(111), or Au(111), can be explained by considering the lower work function of Cu, Ag, and Au compared to Pt. Moreover, the value of the structural mismatch between the oxide and the metal has been suggested to play a role in the stability of Ce 3+ sites at the interface .…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the significant lattice parameter mismatch between most metal surfaces with threefold symmetry and the CeO 2 (111) surface (30–40%), good quality epitaxial cerium oxide films with the fluorite structure and atomically flat terraces have been obtained . Interesting properties of metal/cerium oxide interfaces are evident when the oxide film is ultrathin, i.e., below ≈1 nm thickness, where metastable phases with peculiar properties have been stabilized . For example, Castellarin‐Cudia et al showed that reduced ultrathin ceria films on Rh(111) present an ordered pattern of O vacancies, probably stabilized by the interaction with the substrate, which spatially modulates the oxygen vacancy formation energy within the coincidence cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,28,29 For the periodic surface-slab calculations we used the GGA+U method as implemented by Cococcioni and de Gironcoli, 30 employing a value of the parameter U = 4.5 eV in line with previous works. 24,25,31 Integrals in the Brillouin zone were calculated at the G point. These calculations were performed using the Quantum Espresso package.…”
Section: Computational Details: Model Pt 2+ Sites On Extended Ceria Smentioning
confidence: 99%